Uso de E-Learning y su incidencia en el acompañamiento pedagógico estudiantil para los docentes de la Escuela Rotary Internacional, del cantón Mocache, año 2021 - 2022 - Rendón Moreno, Yuly Shirley (2022)
The document develops a study on the use of E-Learning and its impact on student pedagogical accompaniment for teachers of the International Rotary School, of Mocache, year 2021 - 2022, as an alternative for strengthening student learning. students. The research identifies the importance of the use of these types of virtual platforms where it has been determined that their teachers do not make adequate use. As support for the research, theoretical bases are used that support the development of the project. The research design used is non-experimental and the types of research applied are: descriptive, explanatory and applied for data collection, a survey applied to 27 teachers of the educational establishment was used, from which clear and precise results were obtained from of the teachers who indicate their difficulties in the pedagogical accompaniment provided to the students; from where it is determined to include the use of an E-Learning to follow up on learning, mainly in the area of Social Studies with the purpose of motivating students for new knowledge and improving their academic performance.